Análise da magnitude da influência climática de um remanescente de mata atlântica sobre o seu entorno urbanizado em clima quente-úmido - Amorim, Rafael Ponce de Leon (2011)
The urban spaces environmental quality is determined by the interaction between the natural elements and the man-made changes to adapt the environment to their physical, social and economic needs. In this context, is inserted the urban climate, result of the dialogic relationship between the morphology of the city, the human activities and the various local and global climate factors. The climate change, characteristic of urban space, causes several damages to most cities by increasing the rigors of local climate. In this sense, the study of urban space, in particular, the research about urban climatology, become fundamental to the search for environmental quality, as well as to achieve the energy efficiency in urban areas. In the city, the use of vegetation is an important strategy for mitigation of the local climate, however, is still unknown the potential of this contribution, requiring studies to evaluate the best ways of its application, in accordance with the morphology of the green space and urban space and the local climatic characteristics. The present study analyzed the extent and the magnitude of the influence of the Buraquinho s Forest, in João Pessoa/ PB, in the climatic characteristics of their surroundings by monitoring the temperature and the air s humidity in winter and summer periods, arranged in three transects in downwind of the forest, total of thirteen points of data collection, one of them located in forest interior. It was observed that among the points considered, in the summer, the averages air temperatures were in general 3°C higher than the winter and the relative humidity 15% lower. The temperature differences between points with higher and lower temperatures were similar in both periods, it was observed the main difference at 13h: 3° C in the winter and 2,8 °C in the summer. It was also discovered that the lowest temperatures were obtained in points located on the edge of the forest, whereas the higher temperatures were found in the farthest points, however, it wasn t possible to identify a linear tendency of temperature increase associated to the increased distance from the forest.